CBCT-3D Anthropometric Measurement of Mandibular Bone to Sex Determination in Surabaya Indonesia : a Pilot Study - Riki Kristanto; Eha Renwi Astuti; Daniel Haryono Utomo; Mieke Sylvia Margaretha Amiatun Ruth (Indian Journal of Forensic Medicine & Toxicology, 2021)
Background : Identification of personal is one of important aspects in forensic odontology, because it is oneof the core aspect of forensic science. The one methode of sex determination is measurement of mandibular.The mandibular is a largest and most powerful facial bone in the skull, which is generally resistant topostmortem damage and an important source for personal identification. Previous studies have studiedgender and age prediction using CBCT reconstructive images in a different picture.The objective of thisstudy is to determine the sex determination of os.mandibular using CBCT anthropometric measurements.Materials and Methods : This study involved twenty subjects (10 male and 10 female) with age groupbetween 20 and 35 years. CBCT scans were performed on all subjects, and the data obtained is reconstructedfor 3D viewing. After getting a 3D CBCT scan, measurements were taken on six parameters.Results : The differential mean of male and female is 1,7 mm (Ramus-L), 2,1 mm (Con-Cor), 6,9 mm(BG-Br), 7,3 mm (BIC-Br), 3,5 mm (BH 1st molar) dan 3,8 mm (BH canine). The collected data wereanalyzed using SPSS statistical with Independent T-Test and Logistic Regression test and also DiscrimantFunction. The results showed that of the six parameters, BG-Br and BIC-Br showed 0,0 (P<0,05) statisticallysignificant differences, with the accuracy of the prediction of gender determination on BIC-Br 70% for maleand 80% for female and the overall BG-Br yield of 80% to both group.Conclusion : Sex determination using mandibular with 3D imaging methods can be used and helps in sexdetermination with 80% accuracy.